Ultrahigh resolution of lead zirconate titanate 30/70 domains as imaged by piezoforce microscopy. - Dunn, Steve; Shaw, Christopher P.; Huang, Zhaorong; Whatmore, Roger W. (Cranfield University, 2006)
Piezoforce microscopy (PFM) has been used to determine the domain structure of lead zirconate titanate (PZT) (30/70) on an indium tin oxide (ITO)/glass substrate with a TiO2 boundary layer. The PZT nucleates into the perovskite form in a random crystallographic manner, which leads to a random domain structure in the final film. Using PFM it has been possible to visualize the domain structure of the PZT and determine that the domain structure has features as fine as 8 nm herringbone patterns. The possible impact of these structures for future devices utilizing nanoscale features of PZT and especially FeRAM developments is highlighted.